Evaluating Fisheries Livelihoods: Socio-Economic Dimensions and Management Challenges - Pulungan, Afran Rouzani; Wahyuningsih, Hesti; Delvian (Journal of Environmental and Development Studies, 2024)
Fisheries management, which focuses on using fisheries resources to improve the livelihood of the fishing communities, has led to over-exploitation of fish resources on the east coast of North Sumatra. This has led to a decline in the potential of some fish species, which in turn has affected fishermen's incomes. This study aims to identify the socio-economic conditions of fishermen through the Ecosystem Approach to Fisheries Management (EAFM) and the factors that influence them. The data used are primary and secondary data, collected through observation, interviews, and literature studies. The study involved a sample of 64 fishermen from three locations along the eastern coast of Sumatra: Medan, Serdang Bedagai, and Deli Serdang. This research uses a descriptive qualitative method and the EAFM approach to analyze the social and economic conditions of fishermen in Medan, Deli Serdang, and Serdang Bedagai. The results of this study indicate that there has been a decline in the number of fishermen and the capture fisheries production at the research sites. The score of the social domain scored 55.55 (moderate), while the economic domain scored 66.67 (good) indicating effective but improvable management. The research results show that the indicators of stakeholder participation, utilization of local knowledge for fisheries management, asset ownership, and demand for fishery products are in the good category, while the indicators of fisheries conflicts and fishermen's household income are in the poor category, which needed to be the focus for improvement and enhancement.